UPAYA MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN ALAM (IPA) MELALUI METODE INKUIRI KOMPETENSI DASAR ENERGI PADA SISWA KELAS VII-6 DI SMP NEGERI 10 DEPOK - Edi Nugraha; Ari Gunawan (ITB Swadharma, 2021)
This study aims to increase the independence of students' lateral reasoning which has an impact on improving student learning outcomes in the science class. The learning method applied is the inquiry method which is expected to be able to solve the existing problems. This research has been carried out on 35 students of class VII-6. The action research was carried out for 4 months, from September to December 2016, and was carried out in 3 cycles, each cycle consisting of 3 meetings. Each cycle consists of 4 important activities, namely: Planning, Action, Observation, and Reflection. The implementation in the first cycle is in the form of energy learning and its changes through the inquiry method. The results of the first cycle, observations can be reflected to plan actions in the second cycle. The implementation in cycle II is in the form of learning energy and its changes as well as application in everyday life related to energy through the inquiry method. The implementation of actions in each cycle through the inquiry method by observing student actions, observing teacher performance, and motivating students to participate more with discoveries and experiments. the alternative energy that utilizes everyday materials which are considered partly as unutilized waste. The results of the study indicate that the independence of lateral reasoning through the application of good, directed, and guided inquiry methods can improve learning outcomes in Natural Science (IPA) basic energy competencies and motivate students to be responsible independently and in groups, able to think critically-applicatively which has an impact on student learning outcomes that improve in mastering science concepts as well as practice in learning and being active in making students more daring to study without relying on students who are considered capable and able to solve problems in everyday life that are faced about the context of science and can produce simple works of high creative value, namely the creation of works of energy utilization in everyday life that are converted into other energies.